The Influence of Lifestyle with the Incidence of Hypertension in the Community at the Parmonangan District Health Center - Martalenta Manalu; Anasthasia Sitompul; Hartono; Marlinang Isabella Silalahi; Buenita S (Universitas Muhammadiyah Palu, 2026)
Background: Hypertension remains one of the leading non-communicable diseases worldwide and is closely associated with unhealthy lifestyle behaviors. Lifestyle factors such as dietary habits, physical activity, smoking, caffeine consumption, and family history may contribute to the development of hypertension. This study aimed to analyze the influence of lifestyle on the incidence of hypertension among the community in the working area of the Parmonangan District Health Center. Methods: This quantitative study employed a cross-sectional design and was conducted from April to May 2026. The study population consisted of 203 community members registered at the Parmonangan District Health Center, with a sample of 135 respondents selected using simple random sampling based on the Slovin formula. Data were analyzed using univariate, bivariate (Chi-square test), and multivariate (multiple logistic regression) analyses with a significance level of p < 0.025. Results: The bivariate analysis showed significant relationships between family history (p=0.001), dietary habits (p=0.025), smoking habits (p=0.034), duration of smoking (p=0.007), number of cigarettes smoked per day (p=0.025), and caffeine consumption (p=0.012) with the incidence of hypertension. However, physical activity (p=0.556) and cigarette type (p=0.078) were not significantly associated with hypertension. Multivariate analysis revealed that family history was the strongest predictor of hypertension (OR=22.732; 95% CI=7.736–66.804; p=0.001). Conclusion: Lifestyle factors, particularly dietary habits, smoking behavior, smoking duration, cigarette consumption, and caffeine intake, are associated with the incidence of hypertension. Family history was identified as the most dominant risk factor. Preventive strategies should emphasize healthy lifestyle promotion, smoking cessation, moderation of caffeine intake, healthy dietary practices, regular blood pressure screening, and early intervention for individuals with a family history of hypertension.